Cardiovascular manifestations and patient outcomes following snake envenomation: a pilot study. (January 2019) - John Binu, Aditya; Kumar Mishra, Ajay; Gunasekaran, Karthik; Iyadurai, Ramya
Cardiotoxicity in snake envenomation has not been adequately explored in the literature. This retrospective, observational study analysed clinical profiles and cardiovascular effects (CVE), with associated outcomes, in snake envenomation. Thirty-four patients were recruited between April 2014 and October 2017. Cardiovascular involvement was seen in 24 (70.6%) patients. Electrocardiographic changes included prolonged QTc (62.5%), T-wave inversion (37.5%) and tall T-waves (12.5%). Hospital stay was 7.2 (SD = 5.3) days and 4.4 (SD = 2.4) days in CVE and non-CVE groups respectively ( P value = 0.04). Mechanical ventilation was required only in nine of the CVE group (37.5%; P value = 0.03). Shock was observed in seven patients (20.6%). Two of the patients in the CVE group (5.9%) died ( P value = 1.0); the majority had good outcomes with early administration of anti-venom serum and appropriate supportive measures. Thus, inpatient stay and mechanical ventilation were significantly increased in snake envenomation with CVEs, especially where an underlying co-morbidity existed.